Zoonotic Staphylococcus pseudintermedius sinonasal infections: risk factors and resistance patterns. Issue 7 (25th March 2019) - Ference, Elisabeth H.; Danielian, Arman; Kim, Han Wool; Yoo, Fredrick; Kuan, Edward C.; Suh, Jeffrey D.
Abstract : Background: Staphylococcus pseudintermedius is a Gram‐positive bacteria that colonizes the skin and orifices of healthy canines and felines. It has recently been identified as a cause of sinonasal infections in humans. Methods: This study was a retrospective review of chronic rhinosinusitis (CRS) patients with S pseudintermedius ‒positive sinonasal cultures and comparison to a prospectively collected control sample of patients who underwent culture for acute exacerbation of CRS. Results: Thirty‐three patients with CRS had nasal cultures positive for S pseudintermedius . Of the positive cultures, 82% demonstrated resistance to penicillin, 58% to clindamycin, 45% to trimethoprim‐sulfamethoxazole, 33% to doxycycline, and 27% to oxacillin. Ninety‐seven percent of patients with S pseudintermedius were dog owners. There was no significant difference in age, gender, recent endoscopic sinus surgery, or immunosuppression or deficiency between S pseudintermedius patients and patients undergoing culture for acute exacerbation of CRS, but S pseudintermedius infection was associated with dog ownership ( p < 0.01). S pseudintermedius infection was not associated with behaviors such as a dog sleeping in the bedroom, routinely licking humans, or being diagnosed with a soft tissue infection. Conclusion: Although a rare cause of infection in humans, S pseudintermedius should be considered in sinonasal infections refractory to standard medical management, especially if the patient has regular contact with dogs. S pseudintermedius is not readily identified with routine laboratory diagnostic testing and often demonstrates multidrug resistance, making it a pathogen that is commonly misdiagnosed and difficult to treat.